2008
DOI: 10.1017/s0014479708006406
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Food Security of Low-Resource Farmers: Introducing Horsegram Into Maize-Based Cropping Systems

Abstract: In the hilly areas of eastern Gujarat, western Madhya Pradesh and southern Rajasthan, in western India, farmers are very resource-poor and cultivate small and fragmented land holdings. Maize is their main rainy season (kharif) cereal and it is grown as a rainfed crop in low-fertility fields, often on sloping land that is vulnerable to soil erosion. Its productivity is very low, averaging below 1 t ha −1 . New farm technologies to increase this productivity have to be low cost to be attractive to farmers who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…It is tolerant to drought (Bhardwaj and Yadav 2012), salinity (Reddy et al 1998) and heavy metal stresses (Reddy et al 2005). Horse gram mainly grown in India, Africa, Australia, Burma, Malaysia, Mauritius, and the West Indies (Jeswani and Baldev 1990) under low soil fertility status with few inputs (Witcombe et al 2008). It is adapted to wide range of temperature regimes (Smartt 1985) where other crops invariably fail to survive.…”
Section: Introductionmentioning
confidence: 99%
“…It is tolerant to drought (Bhardwaj and Yadav 2012), salinity (Reddy et al 1998) and heavy metal stresses (Reddy et al 2005). Horse gram mainly grown in India, Africa, Australia, Burma, Malaysia, Mauritius, and the West Indies (Jeswani and Baldev 1990) under low soil fertility status with few inputs (Witcombe et al 2008). It is adapted to wide range of temperature regimes (Smartt 1985) where other crops invariably fail to survive.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely cultivated, however limited attention has been paid to it in terms of genetic development or marketing, so it is still referred to as underutilized, similar to several other crops in this review. Nevertheless, horse gram shows promise because of its drought tolerance and nutritional qualities, along with the fact that it requires few inputs (Bravo et al ., 1999; Mehra and Upadhyaya, 2013; Siddhuraju and Manian, 2007; Witcombe et al ., 2008). It has been shown to be a good source of protein and carbohydrates, and potentially also iron and calcium as long as certain preparation methods are used to break down anti-nutritional compounds (Bravo et al ., 1999; Sudha et al ., 1995).…”
Section: Survey Of Climbing Legume Species That Have Potential To Mitmentioning
confidence: 99%
“…It has been shown to be a good source of protein and carbohydrates, and potentially also iron and calcium as long as certain preparation methods are used to break down anti-nutritional compounds (Bravo et al ., 1999; Sudha et al ., 1995). Participatory trials have been conducted that showed considerable success at addressing some of the challenges of resource poor farmers when horse gram was intercropped with maize in India (Witcombe et al ., 2008). Farmers reported that labour demand decreased due to ground cover provided (particularly female drudgery such as weeding), and they were able to harvest both grain for food and fodder for livestock from the crop (Witcombe et al ., 2008).…”
Section: Survey Of Climbing Legume Species That Have Potential To Mitmentioning
confidence: 99%
See 2 more Smart Citations